Only a Train can Mask another Train - Behrouz Salehian; Melvin Yan (Canadian Journal of Infectious Diseases and Medical Microbiology)
A 36-year-old man presented with fever, abdominal pain and diarrhea reportedly lasting for the past three months. Originally an immigrant from Mexico, he had been living in California for the past four years and made a recent trip back to Guerrero, Mexico. On admission, the patient was febrile (41°C), hypotensive (94/54 mmHg), tachycardic (118 beats/min) and tachypneic (36 breaths/min). Multiple bilateral cervical and axillary lymph nodes were palpated. Other findings included crackles in the bases of both lungs and a large mass in the left hypochondrium.